Estratégias de divulgação científica para crianças através de desenhos animados da TV - Jhonatan Luan de Almeida Xavier; Carolina Brandão Gonçalves (Revista de Estudos e Pesquisas sobre Ensino Tecnológico, 2017)
This work presents the results of a search that had objective to disseminate science to children in the first year of elementary school through cartoons on TV. To achieve the results, a bibliographical and field research was held in a public school in the city of Manaus. The research used a qualitative approach through participant observation over a period of eleven months in the year 2015. How significant results we observed that the science for kids through the TV cartoon is a valuable strategy for developing and democratizing the scientific contents in science education.